2019
DOI: 10.1557/jmr.2019.96
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of CoCrNi medium-entropy alloy produced by gas atomization and spark plasma sintering

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Co, Cr, and Ni). Therefore, no evidence for the development of intermetallic compounds was seen which is also consistent with the literature (Wang et al, 2019;Zhu et al, 2021).…”
Section: Preparation Of Cocrni (Mea)supporting
confidence: 90%
See 2 more Smart Citations
“…Co, Cr, and Ni). Therefore, no evidence for the development of intermetallic compounds was seen which is also consistent with the literature (Wang et al, 2019;Zhu et al, 2021).…”
Section: Preparation Of Cocrni (Mea)supporting
confidence: 90%
“…Considering the importance of this novel class of material, researchers also focused on their corrosion behavior. Wang et al (2019) prepared CoCrNi MEA and evaluated its corrosion behavior in both 1 mol/L NaOH and 0.5 mol/L HCl solutions. He found that NiCoCr MEA offered high corrosion resistance than SUS 304 steel in both environments (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Additive manufacturing (AM): The alloys discussed above were as cast. In recent years, AM technology has been gradually used to prepare HEAs [38,[79][80][81] . AM technology is more efficient and versatile and can directly prepare parts with complex structures.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Besides, the addition of nitrogen was able to markedly improve the anti-corrosion performance due to the high content of chromium oxide within the passivation layer. Wang et al [21] examined the microstructure, mechanical properties, and corrosion behaviour of the as-atomized CoCrNi MEA in 1 M NaOH solution, and found that the MEA consisting of an FCC structure had better corrosion endurance than 304 stainless steel. Nowadays, the corrosion behaviour of CoCrNi MEA has been mainly studied in aqueous solutions of NaCl, H 2 SO 4 , and NaOH.…”
Section: Introductionmentioning
confidence: 99%